2020
DOI: 10.1109/ted.2020.2990125
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Torsional Bending on Reliability and Lifetime of Printed Silver Conductors

Abstract: Capability of high speed and low-cost manufacturing makes the printing techniques very promising approach for largearea flexible electronics mass manufacturing. Due to fast and intensive technology development, the lack of knowledge about the reliability and lifetime of printed electronics is obvious, requiring further investigation. Especially, the effect of torsional bending on lifetime is mostly unexplored field of reliability testing. In this study, a torsional bending test of parallel printed silver condu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…This was considered in a study on the impact of torsional bending on PET supporting R2R screen-printed silver tracks. 71) Samples were twisted by 180°both clockwise and counterclockwise, while measuring four-point resistance and investigating heat patterns with thermography. The tests revealed that length to width ratio of the substrate drastically influenced the sample reliability, where samples with a length to width ratio below three experienced greater magnitude of stress.…”
Section: Reliabilitymentioning
confidence: 99%
“…This was considered in a study on the impact of torsional bending on PET supporting R2R screen-printed silver tracks. 71) Samples were twisted by 180°both clockwise and counterclockwise, while measuring four-point resistance and investigating heat patterns with thermography. The tests revealed that length to width ratio of the substrate drastically influenced the sample reliability, where samples with a length to width ratio below three experienced greater magnitude of stress.…”
Section: Reliabilitymentioning
confidence: 99%
“…During practical applications these sensors operate under intermittent or cyclic mechanical deformations such as bending, stretching, twisting and a combination of these. The sensor response changes with induced stresses during these mechanical movements, and often device failure occurs after repeated stress cycles [17][18][19]. Therefore, greater attention is needed to predict the response of flexible systems under various mechanical deformations [19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Whilst few attempts have been made in this regard, most of the previous studies have focused only on the analysis of mechanical stress distribution and its effect on device performance under tensile and compressive bending and stretching conditions [13,19,[22][23][24][25][26]. Whilst these encouraging works mark a step in the right direction, a very few of them have aimed to understand the stress evolution under twisting (torsional) loading [17,18,27].…”
Section: Introductionmentioning
confidence: 99%